2016
DOI: 10.1371/journal.pone.0150108
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Source of a Humoral Factor of Remote (Pre)Conditioning Cardioprotection

Abstract: Signalling pathways underlying the phenomenon of remote ischaemic preconditioning (RPc) cardioprotection are not completely understood. The existing evidence agrees that intact sensory innervation of the remote tissue/organ is required for the release into the systemic circulation of preconditioning factor(s) capable of protecting a transplanted or isolated heart. However, the source and molecular identities of these factors remain unknown. Since the efficacy of RPc cardioprotection is critically dependent upo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 45 publications
3
56
0
Order By: Relevance
“…An established rat model of myocardial ischaemia/reperfusion injury was used 3 , 13 , 21 . The heart was exposed via a left thoracotomy and a 5–0 monofilament polypropylene suture was passed around the left anterior descending coronary (LAD) artery to induce a temporary occlusion.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…An established rat model of myocardial ischaemia/reperfusion injury was used 3 , 13 , 21 . The heart was exposed via a left thoracotomy and a 5–0 monofilament polypropylene suture was passed around the left anterior descending coronary (LAD) artery to induce a temporary occlusion.…”
Section: Methodsmentioning
confidence: 99%
“…The area at risk and the necrotic area were determined by computerized planimetry, normalized to the weight of each slice, with the degree of necrosis (i.e. infarct size) expressed as the percentage of area at risk, as described 3 , 13 , 21 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cardioprotection by RIPC seems to be dependent on afferent innervation of the remote organ and intact parasympathetic activity, while delayed remote postconditioning relies on different signaling pathways (14). The recent study in rat model have shown that the circulating factors of RIPC are produced and released into the systemic circulation by the visceral organs innervated by the posterior gastric branch of the vagus nerve (15). In brain protection, neuronal involvement in RIPC has been reported in several studies, mainly via a blockade of sensory inputs that reduced the beneficial effects of RIPC (16,17).…”
Section: Neuronal Pathwaymentioning
confidence: 99%